Analisis Pengaruh Tingkat Pengangguran, Indeks Pendidikan dan Persentase Penduduk Miskin terhadap Kesenjangan Ekonomi di Provinsi Jawa Timur - Amelia Fiani Putri; Nur Mulya Ningrum; Fairuzia De Esqirani; Tiara Alindyadini; Adelia Nanda Safitri; Gefira Nurzahira Sugiarto; Radja Trianda Linduaji; Deris Desmawan (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
Many regions in Indonesia face structural problems such as economic inequality. Economic inequality remains a significant obstacle to the development process, especially in developing countries such as Indonesia. The objective of this study is to determine the influence of Unemployment Rate, Education Index, and Poverty Rate on Economic Inequality in East Java Province. This study employs a quantitative method using secondary data analysis from the Central Bureau of Statistics (BPS) for the years 2010–2023. The analysis method used is multiple regression with classical assumption tests. The results of the study indicate that the Education Index and Percentage of Poor Population variables have a significant and positive impact on economic inequality, while the unemployment rate has a significant but negative impact on economic inequality in East Java Province. These findings suggest the need for further analysis of other factors influencing economic inequality to achieve equitable welfare for the community. The implications of this study can serve as a reference for the government in formulating inclusive development policies to reduce economic inequality in East Java.